2020
DOI: 10.1186/s42358-020-00146-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain and sick-leave: a functional magnetic resonance study

Abstract: Background: Chronic low back pain (CLBP) represents a problem in the occupational environment, often associated with disability, sick-leave demands, loss of productivity, anxiety, depression and high socioeconomic cost. The emergence of functional neuroimaging allowed new insights into brain structure and physiology in normality and chronic pain. While occupational related aspects are recognized as important risk factors for chronicity there have not been thus far evaluated by fMRI experiments. The overall obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…This study, however, observed that in patients with chronic pain following SCI, there was overall increased FC between the AI and PI and the frontal pole compared to HC. Other studies have pointed to the role that the prefrontal cortex organizes the affective component of pain with the AI 12,22 . Of note, those with major depressive disorder have been found to have increased FC of the AI with the frontal pole 23 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study, however, observed that in patients with chronic pain following SCI, there was overall increased FC between the AI and PI and the frontal pole compared to HC. Other studies have pointed to the role that the prefrontal cortex organizes the affective component of pain with the AI 12,22 . Of note, those with major depressive disorder have been found to have increased FC of the AI with the frontal pole 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have pointed to the role that the prefrontal cortex organizes the affective component of pain with the AI. 12,22 Of note, those with major depressive disorder have been found to have increased FC of the AI with the frontal pole. 23 Patients with SCI are at increased risk for depression.…”
Section: Increased Fc Of the Ai And Pi With The Frontal Polementioning
confidence: 99%
“…Involvement of lateral frontal pole in pain perception is well established in several neuroimaging and magnetic stimulation studies. [70][71][72] Thus, we examined changes in the overall top-down and bottom-up effective connectivity -with pain perception and placebo response -by selecting nodes at both the highest and lowest levels of the cortical hierarchy in the pain processing pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with irritable bowel syndrome (IBS) display increased activity in the ACC, IC, and prefrontal cortex (PFC) [ 23 ]. Chronic low back pain (CLBP) causes hyperalgesia associated with increased ACC activity and altered functional connectivity, as well as decreased gray matter density in the ACC, PFC, thalamus, brainstem, and somatosensory cortex [ 24 , 25 ]. In cases of fibromyalgia (FM), overall gray matter volume is unchanged but may differ in distribution when comparing healthy to FM patients.…”
Section: Human Studies Of Acc and Icmentioning
confidence: 99%